ALVEOLAR WOUND HEALING IN RATS FED ON HIGH SUCROSE DIET - MARIA A. BARÓ; MARINA ROCAMUNDI; JAVIER VIOTTO; RUTH FERREYRA DE PRATO (2013)
The potential for bone repair is influenced by various biochemical, biomechanical, hormonal, and pathological mechanisms and factors such as diet and its components, all of which govern the behavior and function of the cells responsible for forming new bone. Several authors suggest that a high sucrose diet could change the calcium balance and bone composition in animals, altering hard tissue mineralization. The mechanism by which it occurs is unclear. Alveolar healing following tooth extraction has certain characteristics making this type of wound unique, in both animals and humans. The general aim of this study was to evaluate and quantify the biological response during alveolar healing following tooth extraction in rats fed on high sucrose diets, by means of osteocyte lacunae histomorphometry, counting empty lacunae and measuring areas of bone quiescence, formation and resorption. Forty-two Wistar rats of both sexes were divided into two groups: an experimental group fed on modified Stephan Harris diet (43% sucrose) and a control group fed on standard balanced diet. The animals were anesthetized and their left and right lower molars extracted. They were killed at 0 hours, 14, 28, 60 and 120 days. Samples were fixed, decalcified in EDTA and embedded in paraffin to prepare sections for optical microscopy which were stained with hematoxylin/eosin. Histomorphometric analysis showed significant differences in the size of osteocyte lacunae between groups at 28 and 60 days, with the experimental group having larger lacunae. There were more empty lacunae in the experimental group at 14 days, and no significant difference in the areas of bone activity. A high sucrose diet could modify the morphology and quality of bone tissue formed in the alveolus following tooth extraction.